2009
DOI: 10.1021/jf802418j
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and Green Tea As a Large Source of Antioxidant Polyphenols in the Japanese Population

Abstract: Food and beverages rich in polyphenols with antioxidant activity are highlighted as a potential factor for risk reduction of lifestyle related diseases. This study was conducted to elucidate total polyphenol consumption from beverages in Japanese people. Total polyphenol (TP) contents in beverages were measured using a modified Folin-Ciocalteu method removing the interference of reduced sugars by using reverse-phase column chromatography. A beverage consumption survey was conducted in the Tokyo and Osaka areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 37 publications
4
111
2
2
Order By: Relevance
“…The average polyphenol intake from beverages was within the range of 700-800 mg/d. The polyphenol intake observed in the present study was slightly different from that in our previous study using the survey data in 2004, where children less than 10 y old and elderly individuals aged over 60 y were excluded (8). The polyphenol intake in the present study was equivalent to that in our previous study when estimated in the same age range of the participants.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…The average polyphenol intake from beverages was within the range of 700-800 mg/d. The polyphenol intake observed in the present study was slightly different from that in our previous study using the survey data in 2004, where children less than 10 y old and elderly individuals aged over 60 y were excluded (8). The polyphenol intake in the present study was equivalent to that in our previous study when estimated in the same age range of the participants.…”
Section: Discussioncontrasting
confidence: 93%
“…We calculated the polyphenol intake from beverage consumption data and their polyphenol contents. The polyphenol contents were reported in our previous report (8,9), as measured by a modified Folin-Ciocalteu method (10). The obtained values were expressed as means.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation analysis between the levels of total polyphenols and catechins and EC 50 values were undertaken and both were greatly correlated with DPPH assays (r 2 =0.607 and r 2 =0.654, respectively). Previous studies reported similar correlations between these parameters for green tea and other types of tea products (Fukushima et al 2009;Anesini et al 2008;Karori et al 2010). It was inferred that DPPH radicalscavenging activity was likely due to polyphenols and catechins existed in the Qingzhuan tea extracts.…”
Section: Resultsmentioning
confidence: 53%
“…Coffee contains an abundance of polyphenols, which is the major source of dietary antioxidants [13,14]. Drinking coffee is associated with lower risks of metabolic syndrome, diabetes, and coronary heart disease [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%